MENJAGA LINGKUNGAN DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI MIS AL ISLAM PARIT JAWAI - Khairul Amri Khairul (Atta'dib Jurnal Pendidikan Agama Islam, 2020)
This research is a qualitative study with a descriptive approach. This research was conducted at MIS Al-Islam Parit Jawai, Bukit Segoler Village, Tebas District, Sambas Province. Data taken in research conducted based on the reults of interviews and observations made. The focus of this research is to find out how the application of Islamic religious education in MIS Al-Islam in protecting the environment. Based on the results of research that Islamic religious education in MIS Al-Islam is not only concerned with cognitive aspects but also aspects of affective and psychomotor aspects. The activities carries out by students in protecting the environment are: Planting trees, taking out the trash, and social services carried out with the community. All activities carried out are the implementation of Islamic religious lessons in MIS Al-Islam namely, Aqidah Akhlak, Fiqh, and Al-Quran Hadits. Keywords: Environment, Learning, Islamic Education